Integrated weed management in transplanted rice: Options for addressing labor constraints and improving farmers’ income in Bangladesh - Ahmed, Sharif; Kumar, Virender; Alam, M. Murshedul; Dewan, Mahbubur Rahman; Bhuiyan, Khairul Alam; Miajy, Abu Abdullah; Saha, Abhijit; Singh, Sudhanshu; Timsina, Jagadish; Krupnik, Timothy J. (Cambridge University Press, 2021)
In Bangladesh, weeds in transplanted rice are largely controlled by labor-intensive and costly manual weeding, resulting in inadequate and untimely weed control. Labor scarcity coupled with intensive rice production has triggered increased use of herbicides. These factors warrant a cost-effective and strategic integrated weed management (IWM) approach. On-farm trials with transplanted rice were conducted during monsoon (‘Aman’) season in 2016 and 2017 and winter (‘Boro’) season in 2016 to 2017 in agroecological zones 11 and 12 with ten treatments—seven herbicide-based IWM options, one mechanical weed control-based option, and two checks (farmers’ current weed control practice and weed-free)—to assess effects on weed control, grain yield, labor use, and profitability. Compared to farmers’ practice, herbicide-based IWM options with mefenacet + bensulfuron-methyl as preemergence followed by (fb) either bispyribac-sodium or penoxsulam as postemergence fb one hand-weeding were the most profitable alternatives, with reductions in labor requirement by 11 to 25 person-days ha–1 and in total weed control cost by US$44 to 94 ha–1, resulting in net returns increases by US$54 to 77 ha–1 without compromising on grain yield. In contrast, IWM options with bispyrbac-sodium or penoxsulam as postemergence application fb one hand-weeding reduced yields by 12% to 13% and profits by US$71 to 190 ha–1. The nonchemical option with mechanical weeding fb one hand-weeding performed similarly to farmers’ practice on yield and profitability. We suggest additional research to develop feasible herbicide-free approaches to weed management in transplanted rice that can offer competitive advantages to current practices.